(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
This article describes the specifics of genres and literary expressions used in the work of Nasir ad-Din Burhan ad-Din Rabguzi “Qissas al-Anbiya”, written in the 14th century. The medieval Turkish written heritage developed in the form of religiousidactic and religious-Sufi in the XIII-XIV centuries and thematically expanded. Genre specifics developed. In the Middle Ages, works of art written in Arabic and Persian were translated into Turkish literary language. As a result of literary connections, the artistic features of Turkish written literature increased. Written monuments of the Golden Horde contributed to the development of works of later times. Among the works that influenced the development of written literature in the following centuries of such peoples as Kazakh, Kyrgyz, Uzbek, Bashkir, Nogai, Tatar, Turkmen, etc., were the works of Rabguzi. This literary work of his was widely disseminated in the country under the name «Qissas al-Anbiya» («History of the Prophets»), «Qissas al-Anbiya Rabguzi» («History of the Prophets Rabguzi»), «Qissas al-Anbiya alayhi al-salaam» («History Prophets (peace and blessings be upon him)») and «Kissas Rabguzi» («History of Rabguzi»). The main reason why this literary monument has received a different name is that the Muslim peoples had many religious and didactic works devoted to the history of the prophets, and it was customary to name the work after the author. Therefore, it is important to study the poetics, genre and artistic orientation of this work.